47.7k views
5 votes
Please Help Keep getting 6.4

Please Help Keep getting 6.4-example-1

2 Answers

2 votes

Answer:

radius=3

Explanation:

Given:

x^2 +6x +y^2 - 8y=-16

completing the squares

: x^2 +6x +9 = (x+3)^2

:y^2-8y+16 = (y-4)^2

(x+3)^2 + (y-4)^2 -9-16=-16

(x+3)^2 + (y-4)^2=-16+9+16

(x+3)^2 + (y-4)^2=9

Now comparing with standard equation of circle i.e. (x-h)^2 + (y-k)^2=r^2, we get

origin(h,k)= (-3,4)

r=3 !

User Steve French
by
5.4k points
4 votes

Answer:

r = 3

Explanation:

x^2 + 6x + y^2 - 8y = - 16

Take half the linear term and square it.

x^2 + 6x + (3)^2 + y^2 - 8y + (-4)^2 = - 16

Add the squared amounts to the right.

x^2 + 6x + 9 + y^2 - 8y + 16 = - 16 + 9 + 16

Combine on the right.

x^2 + 6x + 9 + y^2 - 8y + 16 = 9

Represent the 2 quadratics as perfect squares.

(x + 3)^2 + y - 4)^2 = 9

The radius is the square root of 9 which is 3

User Tomako
by
6.3k points